2014
DOI: 10.1111/gwmr.12040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Dual‐Pump Crude‐Oil Recovery System, Bemidji, Minnesota, USA

Abstract: A crude‐oil spill occurred in 1979 when a pipeline burst near Bemidji, MN. In 1998, the pipeline company installed a dual‐pump recovery system designed to remove crude oil remaining in the subsurface at the site. The remediation from 1999 to 2003 resulted in removal of about 115,000 L of crude oil, representing between 36% and 41% of the volume of oil (280,000 to 316,000 L) estimated to be present in 1998. Effects of the 1999 to 2003 remediation on the dissolved plume were evaluated using measurements of oil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Natural attenuation was the primary hydrocarbon loss mechanism until 1999 when a five‐year pump‐and‐treat and oil‐skimming effort was undertaken to remove the LNAPL. The remediation effort resulted in the removal of 36% to 41% of the oil, but it resulted in expansion of the anoxic zone, and much of the oil remains in the subsurface (Delin and Herkelrath ).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Natural attenuation was the primary hydrocarbon loss mechanism until 1999 when a five‐year pump‐and‐treat and oil‐skimming effort was undertaken to remove the LNAPL. The remediation effort resulted in the removal of 36% to 41% of the oil, but it resulted in expansion of the anoxic zone, and much of the oil remains in the subsurface (Delin and Herkelrath ).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Petroleum hydrocarbon contamination of aquifers remains an important problem of environmental relevance due to both accidental spills and leaking underground storage tanks (Nadim et al, 2000; Essaid et al, 2011). During the past decades, substantial efforts have been made to assess the efficacy of methods for remediation of aquifers contaminated by petroleum products (e.g., Delin and Herkelrath, 2014; Höhener and Ponsin, 2014) and to better understand natural attenuation processes of hydrocarbons, both in the source zone, which contains free‐phase product (e.g., Johnson et al, 2006; Lundegard and Johnson, 2006; Ng et al, 2015), and in groundwater plumes, which contain hydrocarbons in dissolved form (e.g., Bockelmann et al, 2003). To facilitate an assessment of the longevity of contaminants in the subsurface, the study of source‐zone natural attenuation (SZNA) and its rates has attracted much attention in recent years (e.g., Chaplin et al, 2002; Sihota et al, 2011).…”
mentioning
confidence: 99%
“…Groundwater sampling showed that the contamination did not spread to a larger area. Based on an extended analysis, a measure with implementation of two remediation wells for a floating oil layer recovery system by dual pump-and-skim technology (Delin and Herkelrath 2014) was applied for the prevention of the spreading and long-term attenuation of the contamination. The dual pumpand-skim technology was composed of two pumps inside each remediation well with a large groundwater pump for the formation of a cone of depression and a small skimmer pump for the temporary pumping of the floating oil layer.…”
Section: Fig 11 -Simulated Groundwater Head With the Location Of Piementioning
confidence: 99%